THE CHANGE OF FUNCTION AND MANAGEMENT OF SITI HINGGIL KASUNANAN PALACE SURAKARTA AS A TOURISM COMMODITY - BRM. Suryo Triono; Cahyani Tunggal Sari (Proceeding IICACS, 2019)
North Siti Hinggil Kasunanan Palace Surakarta is part of Kasunanan Palace Surakarta building is used by citizen of Kraton for formal occasion of the kingdom, such as punggawa or high officials facing the king (nangkil) ceremony, Sekaten ceremony, Mahesa Lawung and the coronation ceremony of the king. The selection of Siti Hinggil as the object of this study considers the important role of Siti Hinggil for the Kraton; Siti Hinggil as